Interassociation consensus statement on sports nutrition models for the provision of nutrition services from registered dietitian nutritionists in collegiate athletics - Lambert, V.; Carbuhn, A.; Culp, A.; Ketterly, J.; Twombley, B.; White, D. (Journal of Athletic Training, 2022)
Collegiate athletic programs are increasingly adding nutrition services to interdisciplinary sports medicine and sports performance departments in response to scientific evidence highlighting nutrition's integral role in supporting athletic performance and overall health. Registered Dietitian Nutritionists (RDNs) specializing in sports dietetics (ie, sports RDNs) and credentialed Board-certified Specialists in Sports Dietetics (CSSDs) are the preferred nutrition service providers for these programs. Their extensive training and proficiency in medical nutrition therapy, education and behavioral counseling, food-service management, exercise physiology, physical performance, and administration, as defined by the "Standards of Practice and "Standards of Professional Performance" for Registered Dietitian Nutritionists in Sports Nutrition and Human Performance," make these practitioners uniquely qualified to deliver the breadth of care required in the collegiate setting. Therefore, this document, guided by a multidisciplinary panel, introduces 4 sports nutrition models through which any collegiate athletic program can deliver sports RDN-directed nutrition services. In each model, the most effective staffing and scope of service are indicated and reviewed. In addition, recommended organizational structures for sports RDNs are provided that best support the delivery of the model's nutrition services in a variety of collegiate athletic programs and organizational settings. Lastly, future research initiatives and nutrition interventions to help improve the standard of care through these sport nutrition models are explored.